Kontribusi Kreativitas dan Supervisi Kepala Sekolah Terhadap Kinerja Guru SMP Negeri Palupuh Kabupaten Agam - Yunisrul , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Teachers have important roles to accomplish the educational goals, and they are expected to show a high level of performance. Performance of the teachers’ was presumably influenced by various factors, such as creativity of teachers and principal supervision. Based on a preliminary field observation, the researcher noticed that High School teachers’ profesionalism in Palupuh Agam was unsatisfactory. Applying a stratified propotional random sampling technique, 30 teachers were selected as the research sample from a population of 62 teachers. A Likert scale model questionnaire was developed to collect data whose validity and reliability had been tested. The data were then analyzed by means of correlation and regression statistical procedures.The result of data analysis indicates that (1) the creativity has contribution as much as 19,6% of teachers’ performance (2) principal supervision contributeas much as 16,6% and (3) the creativity of teacher and prinsipal supervision either joint 16,7% of teacher’s performance. While the achievement level of creativity, teacher’s performance, principal supervision variable are very good